Effect of doping on the magnetic ordering of quasi-one-dimensional antiferromagnets - Zvyagin, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
We have studied theoretically how nonmagnetic dopants, which change the local coupling of spins to the host, affect the low-temperature thermodynamic characteristics of quasi-one-dimensional (Q1D) quantum spin antiferromagnets. Our theory qualitatively and, in some cases, quantitatively describe the behavior of the magnetic susceptibility and specific heat of the Q1D system BaCu2(Si1-x Gex)2 O7. We have shown that in some cases the strong disorder in the distribution of characteristics of magnetic impurities in quantum antiferromagnetic spin chains can be the cause of magnetic ordering, if such chains are weakly coupled to each other, while for homogeneous chains and chains with a weak disorder a small enough coupling between chains does not produce magnetic ordering. For other values of the parameters, magnetic impurities can decrease the Néel temperature compared to that of the homogeneous Q1D spin system.